Guide for the use of immunodiagnostic in sheep applied to the epidemiological surveillance of cystic echinococcosis (Veterinary Science, 2022)
Cystic echinococcosis (CE) is a parasitic zoonosis caused by Echinococcus granulosus sensu lato. Immunodiagnostic techniques such as Western blot (WB) or enzyme-linked immunosorbent assay (ELISA), with different antigens, can be applied to the diagnosis of CE sheep for epidemiological surveillance purposes in control programs. However, its use is limited by the existence of antigenic cross-reactivity between different species of taeniidae present in sheep. Despite this, the usefulness of establishing surveillance systems based on the identification of infection present in a livestock establishment, known as the Epidemiological Unit (UE), has been postulated. A new ELISA diagnostic technique has been developed and validated using the recombinant EgAgB8/2 antigen for the detection of antibodies against E. granulosus, estimating an OD 0.496 as the cut-off value that optimizes diagnostic sensitivity and specificity. To determine the infection in the EU, a Bayesian model was built, executed with a Monte Carlo Markov chain algorithm, which allowed defining the sample sizes for different expected prevalences to ensure that at least two of the samples are truly positive. In this way, the system can be used to identify the prevalence of infection in the area under control measured as a percentage of EU with the presence of infected sheep (infection present) or individually identify the EU with present transmission, given by presence of infected lambs, on which control measures should be intensified.
Keywords: Echinococcosis; Immunodiagnostics; Sheep; Surveillance; Control